Evaluation of the inflammatory markers CCL8, CXCL5, and LIF in patients with anastomotic leakage after colorectal cancer surgery - Klupp, Fee; Schuler, S.; Kahlert, Christoph; Halama, Niels; Franz, Clemens; Mayer, Philipp; Schmidt, Thomas; Ulrich, Alexis (International journal of colorectal disease, 2020)
Anastomotic leakage constitutes a dreaded complication after colorectal surgery, leading to increased morbidity and mortality as well as prolonged hospitalization. Most leakages become clinically apparent about 8 days after surgery; however, early detection is quintessential to reduce complications and to improve patients’ outcome. We therefore investigated the significance of specific protein expression profiles as putative biomarkers, indicating anastomotic leakage.